Social inequalities, health and health care delivery - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2002)
Research on social inequalities has a very long tradition in sociological research, and discussion of the impact of social inequalities on health and health care delivery has long been one of the more important topics covered by medical sociologists. The research presented in this volume varies in its coverage and its approach to issues of social inequality in health and health care delivery. This volume includes both theoretical and quantitative papers, and deals with complex understandings of macro system issues, the impact of the patient and individual factors on health and health care and the impact of the provider and interaction between providers and patients. The first section focuses on macro system issues and includes both theoretical approaches to the topic and quantitative approaches. The second section includes articles with a greater focus on patient characteristics. These articles vary greatly in their coverage, with some focusing on the US as a whole, and others on specific sections of the US or subgroups within the population such as African American women or the elderly. The third section focuses on providers and issues of social inequality and health care delivery. These papers examine issues of gender, race and poverty as examples of sources of inequality in modern societies. In contrast to the second section these papers pay more attention to individual factors and the focus of the chapters is on aspects of health care providers. Research on providers of care is another long, important research tradition within medical sociology. Social Inequalities, Health and Health Care Delivery should be useful reading for medical sociologists and people working in other social science disciplines studying health-related issues. The volume also provides information for health services researchers, policy analysts and public health researchers.